Knockdown of CYP24A1 Aggravates 1α,25(OH)2D3-Inhibited Migration and Invasion of Mouse Ovarian Epithelial Cells by Suppressing EMT - Wang, Ping; Xu, Jiming; You, Weijing; Hou, Yongfeng; Wang, Shuiliang; Ma, Yujie; Tan, Jianming; Zhang, Zengli; Hu, Wentao; Li, Bingyan (Frontiers in Oncology, 2020)
Epithelial-mesenchymal transition (EMT) endows cancer cells with motile and invasive properties. But for ovarian tissues, EMT plays a physiological role in the postovulatory repair of ovary surface epithelial (OSE) cells. Accumulating data indicated that 1α,25(OH)2D3 decreased the migration and invasion of various cancer cells by suppressing EMT. However, it remains unclear whether 1α,25(OH)2D3 could inhibit the process of EMT during different stages of oncogenic transformation in mouse OSE (MOSE) cells. In present study, we found that 1α,25(OH)2D3 significantly reduced the proliferation and invasion of late malignant transformed MOSE (M-L cells) cells by inhibiting EMT both in vitro and in vivo, but not in intermediate transformed (M-I) cells. Importantly, we found that the levels of CYP24A1 in M-I cells was dramatically higher than in M-L cells following treatment with 1α,25(OH)2D3. Furthermore, we demonstrated that, in both M-I and M-L cells with CYP24A1 knockdown, 1α,25(OH)2D3 inhibited the proliferation and invasion, and reduced the expression of N-cadherin, Vimentin, β-catenin and Snail. In addition, knockdown of CYP24A1 suppressed EMT through increasing E-cadherin and decreasing N-cadherin, Vimentin, β-catenin and Snail. These findings provide support for inhibiting CYP24A1 as a potential approach to activate the vitamin D pathway in ovarian cancer prevention and therapy.